SeXX Matters in Multiple Sclerosis - Gilli, Francesca; DiSano, Krista D.; Pachner, Andrew R. (Frontiers in Neurology, 2020)
Multiple sclerosis (MS) is the most common chronic inflammatory and neurodegenerative disease of the central nervous system (CNS). An interesting feature that this debilitating disease shares with many other inflammatory disorders is that susceptibility is higher in females than in males, with the risk of MS being three times higher in women compared to men. Nonetheless, while men have a decreased risk of developing MS, many studies suggest that males have a worse clinical outcome. MS exhibits an apparent sexual dimorphism in both the immune response and the pathophysiology of the CNS damage, ultimately affecting disease susceptibility and progression differently. Overall, women are predisposed to higher rates of inflammatory relapses than men, but men are more likely to manifest signs of disease progression and worse CNS damage. The observed sexual dimorphism in MS may be due to sex hormones and sex chromosomes, acting in parallel or combination. In this review, we outline current knowledge on the sexual dimorphism in MS and discuss the interplay of sex chromosomes, sex hormones, and the immune system in driving MS disease susceptibility and progression.